Causality Analysis of The Money Supply and Interest Rate and Its Effect on Inflation and Investment in Indonesia - Zulfikar, Akbar Lufi; Fajri AF , Muh Shadiqul (The Es Economics and Entrepreneurship, 2023)
This study aims to determine the effect of the money supply and interest rates on inflation and investment in Indonesia without using causality and using causality. In this study, the type of data used was secondary data from 2006 to 2017. The analysis tools used were Path. Money supply without using causality or using causality has a positive and significant effect on inflation in Indonesia. Interest rates without using causality or using causality have a positive and significant effect on investment in Indonesia. Inflation without using causality or using causality has a negative and significant effect on investment in Indonesia. The model without using causality is better or more feasible than the model using causality, seen from the value of the Goodness of Fit model without higher causality compared to the value of the Goodness of Fit criteria model using causality.